PAFPNet News, November 2010 - Secretariat of the Pacific Community (Secretariat of the Pacific Community (SPC), 2010)
Climate change, and its predicted effects on the agriculture and forestry sector, has generated a lot of discussion among PAFPNet members over recent months. This issue of PAFPNet News brings you a number of articles on the topic.